2022
DOI: 10.3746/jkfn.2022.51.9.886
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro and In Vivo Inhibitory Effect of Combined Extracts of Cervus elaphus Antler, Glycyrrhiza uralensis, and Angelica gigas on Benign Prostatic Hyperplasia

Abstract: Combinations of natural products have a number of benefits. We investigated the inhibitory effect of a combination of 50% ethanol extracts of Cervus elaphus antler (CEE), Glycyrrhiza uralensis (GUE), and Angelica gigas (AGE) on benign prostatic hyperplasia (BPH) using BPH-1 cells and testosterone propionate (TP)-induced BPH rats. The combination, called CGA113, inhibited cell proliferation by decreasing the cell viability of BPH-1 cells up to 72.03% more than the individual extracts. In addition, CGA113 signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A previous study has confirmed the mechanism and effect of CAG used in this clinical trial through in vitro and in vivo experiments. 13 Cell experiments proved that CAG could decrease the proliferation of human prostatic hyperplasia epithelial cells significantly. On the other hand, in animal experiments, prostatic hyperplasia could be suppressed by increased Bax protein mRNA expression level and Bax/Bcl-2 ratio in prostate tissues induced by CAG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study has confirmed the mechanism and effect of CAG used in this clinical trial through in vitro and in vivo experiments. 13 Cell experiments proved that CAG could decrease the proliferation of human prostatic hyperplasia epithelial cells significantly. On the other hand, in animal experiments, prostatic hyperplasia could be suppressed by increased Bax protein mRNA expression level and Bax/Bcl-2 ratio in prostate tissues induced by CAG.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a recent animal study, the mRNA expression of Bax protein and the Bax/Bcl2 ratio in the prostate tissue were significantly increased in the Cervi Parvum Cornu complex treatment group used in this study than in the BPH group, suggesting the possible use of Cervi Parvum Cornu complex as a treatment for LUTS caused by BPH. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations